"Folly of the Fiction" and the "Native Taste": Cultural Interfaces in Two Bengali Adaptations of Cymbeline. Issue 1 (7th February 2022) - Sarkar, Abhishek
Abstract: This article examines how two nineteenth‐century Bengali adaptations of Cymbeline transfer Shakespeare's play to a Hindu field of signifiers and reinterpret the elements of tragicomedy according to the worldview of traditional Indian drama. Kusumkumari Natak (1868) by Chandrakali Ghosh, which was enacted before a ticket‐buying audience at the nascent phase of the Bengali public theatre in Kolkata (formerly Calcutta), condenses or rejects much of the action and dialogue of Cymbeline for the sake of economy. For example, it excludes Cloten and the confusion over his beheading and discards Posthumus's dream together with the prophetic riddle. On the other hand, Sushila Birsingha (1868) by Satyendranath Tagore, which was probably never staged, follows the convoluted plot and characterisation of Cymbeline quite closely. Cymbeline would appeal to the Bengali audience because it recalls traditional Hindu tales of reunion and reconciliation, including those of Sakuntala‐Dushyanta (referenced by Kusumkumari Natak ) and Damayanti‐Nala (referenced by Sushila Birsingha ). Moreover, Innogen's ordeals would be compatible with the trope of the abandoned faithful wife (as exemplified by Sita, Sakuntala, Damayanti) in Sanskrit epic and drama. This would also enable the valorisation of wifely fidelity and chastity, a favourite topic of Hindu patriarchal imagination in the nineteenth century. More importantly, the theme of loss and recuperation inherent in Cymbeline accords with the episteme and aesthetics of classical Sanskrit drama, which avoided exploring grave moral challenges and rejected the finality of sufferings (thanks to the doctrines of Vedanta or monistic theism, karma and reincarnation). This article also suggests that Cymbeline fell out of favour with subsequent Bengali translators and playgoers as the taste for tragedy grew among them.